T3 Itaconate drives the resolution of pulmonary fibrosis. (12th November 2019) - Ogger, PP; Ghai, P; Hewitt, RJ; Molyneaux, PL; Maher, TM; Lloyd, CM; Byrne, AJ
Abstract : Introduction and objectives: Idiopathic pulmonary fibrosis (IPF) is a devastating disease with limited therapeutic options. Airway macrophages (AMs) are key components of airway defence and are implicated in the dysregulated wound healing underlying IPF. Itaconate is an endogenous metabolite with antimicrobial and anti-inflammatory potential. Synthesis of itaconate is catalysed by immune-response gene 1 (Irg1) and Irg1/itaconate are increased in macrophages upon stimulation with LPS 1 . We hypothesised that the expression of Irg1/itaconate in AMs is involved in the pathogenesis/resolution of pulmonary fibrosis and manipulation of this pathway could ameliorate disease. Methods: To assess the distribution and expression pattern of Irg1 in healthy/IPF lung, we employed gene expression analysis in AMs, bronchial epithelial cells and lung fibroblasts from IPF patients or controls. To mechanistically interrogate the role of Irg1 in the bleomycin model of pulmonary fibrosis we utilised mice expressing, or lacking Irg1, in addition to therapeutic dosing of exogenous itaconate. Finally, to determine the role of secreted itaconate on the stromal compartment in IPF, primary lung fibroblasts were cultured with itaconate in vitro and proliferation/wound healing was assessed. Results: Irg1 was expressed in AMs, but not epithelial cells or fibroblasts from healthy controls/IPF patients; interestingly, IPF AMs showed reduced expression of Irg1 compared to controls. In the bleomycin model, Irg1 -/- mice had decreased survival, worsened lung function, and increased collagen deposition at the resolution time point (42d post bleomycin) compared to WT mice. Monocyte-recruited AMs (Mo-AMs) showed higher expression of Irg1 compared to tissue-resident AMs (Tr-AMs). Tr-AMs significantly upregulated the expression of fibrosis-related genes in Irg1 -/- compared to WT, while the functional phenotype of monocyte-recruited AMs was not affected by Irg1 -/- . Treatment with itaconate during the fibrotic phase of the bleomycin model improved lung function and decreased gene expression of type IV collagen and fibronectin. In vitro culture of primary human lung fibroblasts with itaconate decreased proliferation and wound healing capacity. Conclusions: Taken together these data indicate that Irg1 -expressing Mo-AMs are essential for the resolution of lung fibrosis and that targeting this pathway may be a viable therapeutic strategy in IPF. Reference: Lampropoulou, Vicky, et al . ( 2016) Cell metabolism .